A deontológiai prioritás: Gondolatrokonság Ny. F. Fjodorov és a »korai szlavofilizmus« képviselői között - Medzibrodszky, Alexandra (Slavia Centralis, 2020)
Importance of Deontology: Thematic Ideas of N. F. Fedorov and Early Slavophile Thinkers
Keywords: N. F. Fedorov; Slavophiles; K. Aksakov; A. Khomyakov; I. Kireevsky; Russian philosophy; Russian intelectual history